Development of hybrid rubber-concrete isolation slab system for 3D vibrations - Nahal Kamil Fayyadh, Fayyadh (2021)
Nowadays, by utilizing structures with various machines and application of structures for operation of variety of trains, trucks or rotary mechanical machineries, the structural components are subjected to multi-directional vibrations as vertical and horizontal cyclic oscillations. The slabs are the main structural components which the dynamic loads, due to vibration generator machines, are imposed to it, and then the load is transferring to the foundation through the girders and columns. Recently, application of the rubber bearings as base isolator systems to dissipate imposed dynamic loads to the structure is frequently considered by design engineers. However, in order to implement the base isolation, it is required to construct each level of building as separated story which highly leads to reduce the lateral strength and stiffness of structure. Moreover, rotary machines induce 3D vibrations and the floating slab system, which implements rubber bearings with compression damping properties, is effective only for damping vertical vibrations rather than horizontal vibrations. Additionally, Regulation No.5 of the Malaysian Regulations for Factories and Machinery (1983) highlighted that any vibrating machinery should not be installed in floors higher than the ground level unless such floor is designed to support the load so imposed thereon. Therefore, the present research aimed to propose a hybrid rubber-concrete isolation slab system (HRCISS) by developing a floating slab system with implementing of high damping rubber in the intermediate layer of concrete slabs. The proposed HRCISS is composed of two upper and lower concrete slab panels with an intermediate layer of square-plan HDR bearings. The initial design details of HRCISS are developed and the performance of the system in reducing the vibrations in both horizontal and vertical directions and the applicability to diminish 3D vibrations is investigated through finite element simulation. After finalizing the design, two prototypes for HRCISS have been manufactured and tested separately, each specimen at a time, under horizontal and vertical cyclic loads by using dynamic actuators in order to evaluate the performance of system and validate the numerical simulation. In order to assess the efficiency of the hybrid system in damping 3D vibrations, it is applied in a half-scale 3-story, 1-bay building and the capability of the system to protect the building from interior vibrations, i.e. machine vibrations as well as its ability to protect the machines from exterior vibrations, such as earthquakes, have been evaluated. The results have shown the effectiveness of the HRCISS in reducing deformations when compared to the conventional 3-story building. Furthermore, utilizing structure with the hybrid system appeared more effective in minimizing lateral drifts and inter-story drifts when it’s installed in lower levels with average 87.33% and 75.8% drop in lateral drift and inter-story drift with respect to the conventional buildings, as well as the remarkable reduction in deflection of the structural slab with 11.1% reduction. The similar results achieved when the 3-story building is imposed to ground motion at the base level as the HRCISS seemed more efficient in reducing the lateral drifts when it’s equipped in the first story, working as a TMD system. Also, the floating slab displaced in less amplitudes in comparison to the structural slab beneath for all the three components of the earthquake, indicating the rubber functioning as a BI system. It can be concluded that the HDR bearings in the HRCISS are influential in controlling 3D vibrations and protecting the structural building from interiorly and exteriorly induced vibrations and hence, the capability to widen the application of vibrating machines in higher stories.